Storm Katie – Rapid cyclogenesis and damaging winds of Easter Monday 2016. (22nd September 2017) - Ramsdale, Steven; Kelly, Jason
Abstract : Storm Katie was the 11th officially named storm of the winter and spring seasons of 2015/16, affecting primarily southern parts of England on Easter Monday (28 March 2016). The potential for disruptive winds was identified at a relatively long lead time, with communication to this effect being made by the Met Office 7 days before the storm arrived in the UK. This article looks at the forecasts and warnings in advance of the storm, examines the evolution of the system with a brief discussion on the application of conceptual models and then rounds up with the impacts from the associated wind, rain and snow. Abstract : Storm Katie was the 11th officially named storm of the autumn, winter and spring seasons of 2015/2016 as part of the storm naming program introduced by the Met Office and Met Éireann. This article looks at the storm from initial identification in the medium range to evolution and associated impacts.